PERENCANAAN DETEKTOR KONTAMINASI BAHAN BAKAR PADA TANGKI BULANAN (MAIN FUEL TANK) GENSET DI BANDAR UDARA ADISUTJIPTO YOGYAKARTA - Fatra, Oka; N.A.N, Muhammad Samudera; Pramesti, Maharani Dewi; Djokja, Mochammad Rizki Bachtiar; Palapessy, Benyamin Verdy; Yanti, Putu Aprellia Heryka (Program Studi Teknik Mekanikal Bandar Udara, 2023)
The Genset, which is an extension of the generator set, served as a replacement when PLN (National Electric Company) turned off. The generator consists of a generator/alternator and a machine/machine. These generators use solar fuel (diesel) or gasoline. The fuel used must be of good quality because if contaminated with other substances, it will cause damage and can be fatal because the airport does not have electricity reserves.The issues discussed include how the generator works, what to do if damage occurs, and how to deal with fuel contamination. In this study, research methods directly by jumping into the field are used to perform observations and analyses.